Synthesis of Bis(1,2,3-triazolyl)alkanes in Superbasic and Solvent-Free Conditions - Roman D. Marchenko; Andrei S. Potapov (Molbank, 2023)
Nucleophilic substitution reactions between 1,2,3-triazole and dibromomethane or 1,2-dirbomoethane in a superbasic medium potassium hydroxide–dimethyl sulfoxide gave mixtures of the isomeric bis(1,2,3-triazolyl)alkanes, in which (1,2,3-triazol-1-yl)(1,2,3-triazol-2-yl)alkanes and bis(1,2,3-triazol-2-yl)alkanes were the dominating products, while bis(triazol-1-yl)alkanes were detected only in trace amounts. The same products could also be obtained under solvent-free conditions in a neat reaction mixture. The proposed methods are economically feasible, do not require using toxic solvents or catalysts, and make the (1,2,3-triazol-2-yl)-derivatives, inaccessible by alkyne-azide cycloaddition (click) reactions, readily available.